Chromosomal similarities and differences among three sibling species of the Acalles echinatus group (Coleoptera, Curculionidae, Cryptorhynchinae) - Lachowska, Dorota; Rożek, Maria; Holecovà, Milada (Zootaxa, 2009)
In order to clarify the taxonomic position of three sibling species of weevils from the Acalles echinatus group, A. echinatus, A. fallax and A. petryszaki, cytogenetic relationships are investigated by studying the mitotic and meiotic chromosomes, including the localisation of heterochromatin by C-banding, as well as the localisation of NORs by silver impregnation. These sources of data are congruent and strongly support that the examined species are closely related. All examined species are characterised by a karyotype of the same chromosome number and sex determination system but with different morphology of chromosomes. All the analysed features, such as the centromeric index, relative length, Cbands and NORs, show that the structure of the karyotype of A. echinatus is more similar to that of A. petryszaki, whereas the karyotype of A. fallax is divergent. The higher chromosome number (2n = 30) in relation to the modal formula in Curculionidae (2n = 22) suggests that karyotype evolution in these species could have occurred by centric fissions of metacentric elements leading to acrocentry.